Особливості адресованості в офіційному та неофіційному типах дискурсу - Семенюк, Антоніна Афанасіївна; Хникіна, Оксана Олександрівна; Semeniuk, Antonina A.; Khnykina, Oksana O. (My University, 2017)
У статті висвітлено роль фактора адресата в офіційному (судовому дискурсі обвинувачення) та неофіційному (сімейному) типах дискурсу. Визначено комунікативно-прагматичні параметри адресата як мовної особистості. Розроблено типологію адресата та проаналізовано вербалізацію адресованості в досліджуваних типах дискурсу. The article highlights the role of the addressee factor in the official (judicial discourse of accusation) and non-official (family) types of discourse. The communicative-pragmatic parameters of the recipient as a language personality are defined. The typology of the addressee is developed and the addressing verbalization in the types of discourse under investigation are analyzed.
The peculiarities of addressing in the official and non-official discourse
Keywords: addressing; addressee; family discourse; court discourse of accusation; адресованість; адресат; адресант; сімейний дискурс; судовий дискурс обвинувачення